KONSEP UANG DALAM ISLAM - Rizky Amelia Fathia (Kajian Hukum, 2018)
In Islamic economics, money has the main function as a medium of exchange (medium of exchanges) and a unit of account (unit of account). Although in practice it is still permissible to use money as a store of deferred value and payment standards. So it must review the principles according to the Islamic economic perspective. In comparison with the conventional economic theory of Islamic capitalism, talking about money as a means of exchange and store of value, but money is not a commodity. Money becomes useful only if it is exchanged with the stated object or if it is used to buy services. Therefore money cannot be sold or purchased on credit. People need to understand the policy of the Prophet Muhammad, that not only announce interest on loans as illegitimate but also prohibit the exchange of money and other valuables for unequal exchanges, and delay payments if the merchandise or currency is not the same . The effect is to prevent the interest of money entering the economic system through unknown methods. Keywords: Money, Economy, Islamic Principles